Dukungan Sosial Orangtua Terhadap Anak Disabilitas Netra Dalam Pencapaian Prestasi Akademik - Adelia Octaviani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
A person's reduced ability to see images while performing daily activities or the malfunctioning of their sense of sight is referred to as a visual disability. Children with visual impairments are entitled to a supportive education that will help them excel in school. Parental social support can help with this. The purpose of this study is to find out the social support that parents provide to their children with visual disabilities to help them achieve academically, as well as the factors that hinder and support the implementation of social support. This study was conducted using a qualitative method, descriptive research type, with purposive sampling with four respondents. Interviews, observation, and documentation were used to collect data. The results showed that academic achievement of children with visual disabilities is influenced by parental social support, which includes emotional support, appreciation, instrumental support, information support, and group support. The development of academic skills and cognitive development is influenced by the characteristics of visual disability. This relates to the important role played by parents and SLB - A Pembina Tingkat Nasional school in educating their children who have visual disabilities. Parents provide information or advice verbally or nonverbally that has a positive impact on the action or emotional in the activity.